2022
DOI: 10.3390/ijms23126413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photobiomodulation in Suppression of Oxidative Stress on Retinal Pigment Epithelium

Abstract: As the world undergoes aging, the number of age-related diseases has increased. One of them is disease related to retinal pigment epithelium (RPE) degeneration, such as age-related macular degeneration, causing vision loss without physical damage in the ocular system. It is the leading cause of blindness, with no cure. Although the exact pathogenesis is still unknown, the research shows that oxidative stress is one of the risk factors. Various molecules have been reported as anti-oxidative materials; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…To explore the effects of multiwavelength PBM on the retina, we established an in vivo model of AMD induced by NaIO 3 . It is known that PBM of various wavelengths reduces ROS levels and thus cellular oxidative stress [24,46]. In our in vitro experiment, although we observed that multi-wavelength PBM tends to decrease ROS changes in RPE cells after oxidative stress-induced by hydrogen peroxide, we did not obtain significant results (Figure S2).…”
Section: Discussioncontrasting
confidence: 56%
“…To explore the effects of multiwavelength PBM on the retina, we established an in vivo model of AMD induced by NaIO 3 . It is known that PBM of various wavelengths reduces ROS levels and thus cellular oxidative stress [24,46]. In our in vitro experiment, although we observed that multi-wavelength PBM tends to decrease ROS changes in RPE cells after oxidative stress-induced by hydrogen peroxide, we did not obtain significant results (Figure S2).…”
Section: Discussioncontrasting
confidence: 56%
“…In agreement with this, our results showed that the ZO‐1 and Claudin 5 were decreased both in vitro and in vivo stroke models, and that PBMT could reverse these changes. Other studies also reported that PBMT increases the TJ proteins in retinal pigment epithelium cell 46 . The mechanism of PBMT predominantly involves the stimulation of Cytochrome C oxidase within the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies also reported that PBMT increases the TJ proteins in retinal pigment epithelium cell. 46 The mechanism of PBMT triggers the extracellular signal-regulated kinase/cAMP-responsive element-binding signaling pathway. 47 In diabetic fibroblast cells, PBMT activates the PI3K/AKT pathway, 48 and it has been observed to promote neural stem cells via the AKT/GSK-3β/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the increased ROS may function as a second messenger to regulate various signaling pathways affecting gene expression [ 42 ]. However, Kim et al found that PBM pretreatment inhibited ROS production in a hypoxia model of retinal pigmental cells (RPE) [ 43 ]. Huang et al also demonstrated that low-level laser treatment (LLLT) increased ROS in normal neurons but decreased ROS in oxidatively stressed neurons, suggesting that this might be related to the fact that low-level laser can increase mitochondrial membrane potential (MMP).…”
Section: Potential Molecular Mechanisms Of Pbm For Treating Retinal D...mentioning
confidence: 99%